Splenic rupture as a rare complication of infectious mononucleosis – case report - Błaszczyszyn, Katarzyna; Orzechowski, Maciej; Wójtowicz, Aleksander; Orzechowski, Janusz (Quality in Sport, 2024)
Infectious mononucleosis, caused by the Epstein-Barr virus, is a contagious disease primarily transmitted through bodily fluids, such as saliva. It is characterized by flu-like prodromal symptoms, followed by the tonsils enlargement, lymphadenopathy, and hepatosplenomegaly. Complications although rare, may include thrombocytopenia, anemia, encephalitis, myocarditis, or pancreatitis. One of the most dangerous is splenic rupture, which occurs in 0.1% to 0.5% of patients diagnosed with infectious mononucleosis. We present the case of an 18-year-old patient, admitted to the general surgery department with acute abdominal pain, later diagnosed with Epstein-Barr virus-related splenic rupture unrelated to any trauma. The subsequent laboratory tests revealed leukocytosis, anemia, and abnormal liver function. Imaging revealed free fluid and an enlarged spleen, prompting laparoscopy, later converted to laparotomy due to surgical complexities. Splenectomy was performed, resulting in clinical improvement. Following effective treatment and implemented interventions, the patient was discharged after 7 days with specific postoperative instructions.